A Comprehensive Review of Interdepartmental Collaboration for Enhanced Patient Care - AL HARITH, Abdullah Awed Mohammed; Alsaed, Yousef Yahya Nasser; Al-Yami, Ahmed Mohammed Ahmed; Al-Yami, Hussein Hamad Mohammed; Almansour, Salem Hassan Rashed; Al Mansour, Abdullah Hassan Rashed; Al Nasser, Nasser Salem Nasser; Alsari, Mansour Ahmed Salem; al sari, Abdullah Ahmed; Al Mokalas, Sajwa Falah Hussen; Alwadii, Ohood Salem Yahia (Journal of Ecohumanism, 2024)
Integrated communication is a core activity that plays a significant role in today's healthcare organizations, as it offers a solution to how departments cooperate to improve patient services given the dynamic patient needs, available resources, and organizational system efficiency. All of these aspects of interdepartmental healthcare challenges and strategies of healthcare organizations are well presented in the literature review. These are communication as an element, leadership, the effective use of technology, and interdisciplinary working. Many practical instances, examples, and facts cited while sharing facts and figures in this review emphasize the significance of cross-function integration. It also explained future possible research topics such as the role of AI, hospital networks, and follow-up patient models. The findings raise awareness of the role of interdepartmental cooperation in providing good quality patient-oriented care and increasing healthcare.